1989
DOI: 10.1148/radiology.172.2.2546175
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for recurrence and cosmesis in 393 patients after radiation therapy for early mammary carcinoma.

Abstract: Between 1978 and 1985, 393 of 2,765 (14%) patients with operable cancer of the breast (clinical stage T0-3N0-2M0) were irradiated after excisional biopsy and staging axillary dissection. Of 77 patients with microscopic axillary metastases, 68 received systemic adjuvant therapy. Treatment failed locally in 26 cases, and there were seven patients with distant metastasis. The three major factors for increased local treatment failure were (a) age below 40 years (P = .003), (b) negative estrogen receptor assay resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…The most common indication for using a boost during that period was the presence of close, positive, or unknown margins, as has been reported by other studies. 45,46 The use of a boost had no effect on IBTR-free survival rates in multivariate analyses. However, our study is limited because of its retrospective nature and its small sample size compared with the sample size of a prospective trial reported by Romestaing et al 48 Because Romestaing's randomized trial showed a benefit in improving local control, our contemporary approach changed to use a boost routinely in every patient undergoing breast conservation after 1997.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The most common indication for using a boost during that period was the presence of close, positive, or unknown margins, as has been reported by other studies. 45,46 The use of a boost had no effect on IBTR-free survival rates in multivariate analyses. However, our study is limited because of its retrospective nature and its small sample size compared with the sample size of a prospective trial reported by Romestaing et al 48 Because Romestaing's randomized trial showed a benefit in improving local control, our contemporary approach changed to use a boost routinely in every patient undergoing breast conservation after 1997.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies, including NSABP B-06, have reported excellent results without the boost for patients with negative margins after BCS. 1,[45][46][47] However, a prospective randomized trial 48 of patients with negative margins showed that the addition of a boost dose to whole-breast irradiation resulted in a 20% reduction in the local recurrence rate at 5 years (4.5% for the no-boost group vs 3.6% for the boost group, P ϭ 0.044). In the study reported here, use of a radiation boost significantly declined for patients treated from 1994 to 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, breastconserving surgery requires excision of all gross tumor and subsequent radiation therapy to ensure sufficient local control [1,2]. However, the extent of surgical resection beyond gross excision, and specifically the importance of microscopically negative margins, remains unclear [3][4][5]. It is generally accepted that the presence of microscopically positive margins requires reexcision [4].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the adverse effects of positive margins on overall outcome of the patients many radiation oncologists have escalated the boost dose to increase total dose to tumour bed [14,56,58,60]. Although in all these studies, patients with positive margins underwent re-excision or revision surgery, the boost doses to tumour bed were escalated to 20 Gy.…”
Section: Pathological Prognostic Factorsmentioning
confidence: 99%
“…Total radiation dose to affected breast and tumour bed is proportionately related to relapse free survival [40,41,56,61]. Other factors which significantly influence disease free survival are administration of chemotherapy and hormonal therapy.…”
Section: Treatment Related Factorsmentioning
confidence: 99%